3×2-16x-7=5

Move 5 to the left side of the equation by subtracting it from both sides.

3×2-16x-7-5=0

Subtract 5 from -7.

3×2-16x-12=0

For a polynomial of the form ax2+bx+c, rewrite the middle term as a sum of two terms whose product is a⋅c=3⋅-12=-36 and whose sum is b=-16.

Factor -16 out of -16x.

3×2-16x-12=0

Rewrite -16 as 2 plus -18

3×2+(2-18)x-12=0

Apply the distributive property.

3×2+2x-18x-12=0

3×2+2x-18x-12=0

Factor out the greatest common factor from each group.

Group the first two terms and the last two terms.

(3×2+2x)-18x-12=0

Factor out the greatest common factor (GCF) from each group.

x(3x+2)-6(3x+2)=0

x(3x+2)-6(3x+2)=0

Factor the polynomial by factoring out the greatest common factor, 3x+2.

(3x+2)(x-6)=0

(3x+2)(x-6)=0

If any individual factor on the left side of the equation is equal to 0, the entire expression will be equal to 0.

3x+2=0

x-6=0

Set the first factor equal to 0.

3x+2=0

Subtract 2 from both sides of the equation.

3x=-2

Divide each term by 3 and simplify.

Divide each term in 3x=-2 by 3.

3×3=-23

Cancel the common factor of 3.

Cancel the common factor.

3×3=-23

Divide x by 1.

x=-23

x=-23

Move the negative in front of the fraction.

x=-23

x=-23

x=-23

Set the next factor equal to 0.

x-6=0

Add 6 to both sides of the equation.

x=6

x=6

The final solution is all the values that make (3x+2)(x-6)=0 true.

x=-23,6

Solve using the Square Root Property 3x^2-16x-7=5